2010
DOI: 10.1002/ejlt.201000044
|View full text |Cite
|
Sign up to set email alerts
|

Novel antioxidants in food quality preservation and health promotion

Abstract: Autoxidation in food and biological systems is responsible for a multitude of adverse effects and implications in human health as well as in food stability and preservation. Antioxidants play a major role in preventing or delaying autoxidation and have attracted much attention as food stabilizers, dietary supplements and natural health products. Both synthetic and natural antioxidants are widely used in food products and an ever increasing number of research papers have appeared in the recent literature on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
269
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 382 publications
(275 citation statements)
references
References 97 publications
2
269
0
4
Order By: Relevance
“…Antioxidant defenses mechanism plays an important role in checking the level of ROS and RNS in the living systems (Lai et al, 2001;Gulcin et al, 2002). Enzymatic antioxidants remove free radicals by converting various ROS and RNS into H 2 O 2 and water while non-enzymatic antioxidants perform their defensives mechanisms by breaking free radical chain reactions (Shahidi and Zhong, 2010 Similarly, it has been reported that SOD, an antioxidant enzyme, plays an important role in quenching ROS (Imlay, 2013), thereby converting superoxide anions into H 2 O 2 which are then converted to oxygen (O 2 ) and water (H 2 O) after being catalyzed by catalase enzymes. From the results, it can be concluded that the antioxidant defense properties of cAuNps are significantly higher as compared to curcumin as evident from both SOD and catalase assays.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant defenses mechanism plays an important role in checking the level of ROS and RNS in the living systems (Lai et al, 2001;Gulcin et al, 2002). Enzymatic antioxidants remove free radicals by converting various ROS and RNS into H 2 O 2 and water while non-enzymatic antioxidants perform their defensives mechanisms by breaking free radical chain reactions (Shahidi and Zhong, 2010 Similarly, it has been reported that SOD, an antioxidant enzyme, plays an important role in quenching ROS (Imlay, 2013), thereby converting superoxide anions into H 2 O 2 which are then converted to oxygen (O 2 ) and water (H 2 O) after being catalyzed by catalase enzymes. From the results, it can be concluded that the antioxidant defense properties of cAuNps are significantly higher as compared to curcumin as evident from both SOD and catalase assays.…”
Section: Discussionmentioning
confidence: 99%
“…Certain amino acid structures have been correlated with high antioxidant properties. These include amino acids with sulfur residues (Cys and Met) and aromatic structures (Trp, Tyr, His and Phe) [19,48,60,73,75]. Phenol and indole groups in amino acids can act as potential hydrogen donors [70,73,75].…”
Section: Discussionmentioning
confidence: 99%
“…Milk proteins, peptide sequences encrypted within the primary structures of the milk proteins and amino acids have also been associated with the regulation of postprandial glycaemia and insulin secretion in normoglycaemic and type 2 diabetic subjects [24,26,56,57,61,72]. Different studies have demonstrated the anti-oxidative role of milk proteins and peptides [19,53,70,75,83]. A fraction from human milk enriched in Trp has been identified for its high scavenging activity in vitro [84].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of substances have been identified as antioxidants exerting their oxidationinhibitory effects by different mechanisms [1,2]. However, the list of lipophilic natural oxidants is limited.…”
mentioning
confidence: 99%